A Correlation Between Students’ Intelligence Quotient (IQ) and Their Writing Ability for the Eighth Grade - Muhammad Zainul Muttaqin Eka Wiratna; Hidayatul Hamdiah (CV. Creative Tugu Pena, 2020)
This article was focused on the correlation between students’ intelligence quotient (IQ) and their writing ability. The purpose of the study was to find out whether there is any positive correlation between students’ intelligence quotient (IQ) and their writing ability. This study was quantitative research. The sample was 25 students. To collect the data, the researchers informed the students’ an instrument in multiple-choice tests as many as 15 questions for intelligence quotient (IQ) and an essay which is a form in the descriptive text for writing ability. Descriptive statistic and hypothesis testing were used to analyze the data in this research. Furthermore, the mean score of students’ intelligence quotient (IQ) was 78.00 and 66.24 was the mean score of students’ writing. Moreover, the Standard Deviation of intelligence quotient (IQ)was 3.464 and writing was 4.772. The present researcher found out the result of the correlation coefficient was .403 at p =.046 which was lower than 0.05 (as the standard significance level in SPSS) at two tails. This implied the first Ho (null hypothesis) was rejected and first Ha (alternative hypothesis) was accepted. It means that there was a correlation between students’ intelligence quotient (IQ) and their writing ability for the eighth graders of MTs Ihya’ Ulumuddin. Keywords: Intelligence Quotient (IQ), Writing Ability, and Intelligence